Integrating the Talaqqiyan Fikriyan and Sorogan Methods in Qur’anic Education to Develop Students’ Moral and Spiritual Character - Suciati; Syaifuddin, Mohammad; Khozin (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2025)
This qualitative study explored the integration of the Talaqqiyan Fikriyan method and the Sorogan model in Qur'anic education at Islamic Center eLKISI, Mojokerto, East Java. The study employed observation, interviews, and documentation over a period of three months to gather comprehensive data on the implementation and outcomes of the integrated method. The results indicate improvements in students' discipline, honesty, empathy, and spiritual awareness. The integration of reflective thinking and individualized instruction led to improvements ranging from 18% to 33% in students’ moral and spiritual indicators. Teachers also observed stronger student motivation and improved teacher-student interactions. These findings underscore the relevance of traditional Islamic pedagogy in enhancing character-based education.